Florid hyperandrogenism due to a benign adrenocortical adenoma. (30th July 2018) - LaVoie, Melanie; Constantinides, Vasilis; Robin, Noel; Kyriacou, Angelos
Abstract : A 26-year-old woman with a history of polycystic ovarian syndrome presented with secondary amenorrhea, worsening hirsutism, acne, deepening of voice and unexplained 10–20 kg weight gain. Her Ferriman-Gallway hirsutism score was 12 with cystic facial acne and increased masculine phenotype. Urine Beta-Human Chorionic Gonadotropins (bHCG) was negative. She had elevated serum testosterone of 551 ng/dL, androstenedione at 7.46 ng/mL and dehydroepiandrosterone sulfate (DHEAS) at 4243 µg/L. Overnight dexamethasone suppression test showed mildly unsuppressed cortisol (2.89 µg/dL). Urinary free cortisol along with paired serum cortisol and adrenocorticotrophic hormone (ACTH) tests were normal (55.4 µg/24 hours, 13.44 mcg/dL, 30.4 pg/mL respectively). Her leutinizing hormone (LH) was low(<0.1 mIU/mL), follicle stimulating hormone (FSH) low/normal (1.41 mIU/mL) with sex hormone binding globulin (SHBG) level 45nmol/L and the rest of the pituitary and adrenal workup was unremarkable. Thyroid stimulating hormone (TSH) was 2.15mU/mL. MRI revealed a 3.1 cm, indeterminate but well-defined left adrenal lesion and polycystic ovaries without abdominal lymphadenopathy. Given radiological appearances and despite biochemical concerns for adrenocortical malignancy, a multidisciplinary team meeting decision was made to proceed with laparoscopic adrenalectomy. Histology was consistent with a benign adenoma. Postoperatively, there was clinical and biochemical resolution of the disease.